2017
DOI: 10.3224/zff.v29i1.04
|View full text |Cite
|
Sign up to set email alerts
|

Aktive Vaterschaft in Organisationen – Anspruchsbewusstsein und verborgene Regeln in Unternehmenskulturen

Abstract: Anspruchsbewusstsein und verborgene Regeln in Unternehmenskulturen Involved fatherhood in work organizations Sense of entitlement and hidden rules in organizational cultures Zusammenfassung: Das Verständnis von Vaterschaft hat in den letzten Jahren einen Wandel erfahren, der sich u.a. in veränderten Leitbildern aktiver Vaterschaft und entsprechenden politischen Maßnahmen äußert. Viele Arbeitsorganisationen weiten ihre Vereinbarkeitsprogramme auf Väter aus. Organisationskulturen enthalten jedoch immer noch late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Moreover, the prevalence of the ideal worker norm may also contribute to fathers' reluctance to take leave (von Alemann et al 2017). In this vein, Kaufman (2018) found that a low uptake of parental leave was associated with fathers' perception of an unsupportive workplace and hence backed up the finding by Thompson et al (2005) that fathers in Britain who had very supportive bosses took longer leave on average than those whose bosses were not at all supportive.…”
Section: Organizations and Gender Inequality In Parental Leave Usementioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the prevalence of the ideal worker norm may also contribute to fathers' reluctance to take leave (von Alemann et al 2017). In this vein, Kaufman (2018) found that a low uptake of parental leave was associated with fathers' perception of an unsupportive workplace and hence backed up the finding by Thompson et al (2005) that fathers in Britain who had very supportive bosses took longer leave on average than those whose bosses were not at all supportive.…”
Section: Organizations and Gender Inequality In Parental Leave Usementioning
confidence: 94%
“…Most of the existing studies on the relationship between workplace characteristics and fathers' parental leave have been conducted in Nordic countries. Empirical work on the relationship between workplace characteristics and fathers' uptake and length of leave in Germany is still relatively scarce and has, thus far, predominantly been qualitative (von Alemann et al 2017;Aunkofer et al 2018;Neumann and Meuser 2017). Hence, while we know that the workplace matters, we do not know which workplace characteristics contribute to the persistent gender gap in the uptake of parental leave.…”
Section: Organizations and Gender Inequality In Parental Leave Usementioning
confidence: 99%
“…Nevertheless, it is mostly companies or hierarchical levels with high shares of women that implement and expect to profit from these family-friendly measures (Bergmann and Schiffbänker 2016;Frodermann et al 2018). Although there is an increasing awareness that also men and fathers have to be a central target group of these measures, it is mostly women and mothers who feel entitled and claim certain benefits or rights (Alemann et al 2017). Employers and companies view family-friendly policies for fathers primarily as an economic necessity.…”
Section: Parents At Their Workplace-general Evidence and Research Gapmentioning
confidence: 99%
“…Factors constituting the frame of reference for gender-equality policies for women, such as equality or justice, hardly play a role (Liebig and Kron 2017). On the one hand, organizations offer services for parents to better reconcile their employment with their parental responsibilities, while on the other hand, they reward long working hours and availability with good salaries and career opportunities (Alemann et al 2017). Consequently, mothers continue to have the main responsibility for unpaid care and family work.…”
Section: Parents At Their Workplace-general Evidence and Research Gapmentioning
confidence: 99%
See 1 more Smart Citation